Kajian Model Springate Pada Kelompok Saham Jakarta Islamic Index Periode 2013–2017 - Windu Anggara; M. Syukri Albani Nasution (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2021)
This  study  aims  to  find  out  and  analyze  the  health  condition  of  the company  based  on  the  magnitude  of  the  predicted  value  using  financial  ratios  in the  Springate  model.  The  research  method  used  is  descriptive  analysis  method with  a  quantitative  approach.  The  research  population  is  all  companies  listed  in Jakarta  Islamic  Index  (JII),  amounting  to  30  companies,  using  purposive sampling.  The  analysis  technique  used  is  the  analysis  of  financial  statements  with the  Springate  model  (S-Score)  which  aims  to  find  out  companies  that  experience financial  distress  and  bankruptcy.  The  results  showed  that  there  were  several companies  in  2013  and  2014  that  experienced  bankruptcy,  namely  16.67%,  then increased  to  26.67%  in  2016,  and  the  most  significant  occurred  in  2015  and  2017, namely  30.00%